Additions to the aphid fauna of Wrangel Island due to climate change withredescription of the oviparous female of Pterocomma groenlandicum Hille Ris Lambers, 1952 (Hemiptera, Aphidoidea) - Khruleva, Olga A.; Stekolshchikov, Andrey V. (Zootaxa, 2019)
The article contains new data on the Aphidoidea of Wrangel Island collected in 2015. Previously, at least four species were known. Two of them, Aphis polaris Stekolshchikov et Khruleva, 2014 and Metopolophium sabihae Prior, 1976, were regularly observed on the island in the 1980s and 1990s. Pterocomma groenlandicum Hille Ris Lambers, 1952 and Myzus (Nectarosiphon) polaris Hille Ris Lambers, 1952, were first collected in 2006. In 2015 three more species were found: Brachycaudus (Mordvilkomemor) rumexicolens (Patch, 1917), Cavariella aegopodii (Scopoli, 1763), and Pemphigus saliciradicis (Börner, 1950). This last species represents a first record for the territory of Russia whereas C. aegopodii had not previously been collected in tundra landscapes. In 2015, a total of seven aphid species were collected. For one of the four previously noted species, M. sabihae, a sharp increase in its abundance is recorded. We propose that the increase in aphid species diversity is due to climate warming in the Russian High Arctic. A detailed redescription of the oviparous female of P. groenlandicum is also provided.